Telling stories of terrorism: a framework for applying narrative approaches to the study of militant's self-accounts. (2nd September 2019) - Copeland, Simon
ABSTRACT: Narrative has recently garnered in much attention in the study of terrorism but remains poorly understood. This paper offers some initial steps towards translating the promise of narrative approaches into a set of steps for systematically analysing and understanding terrorists' own accounts of their engagement with extremism and militancy. This approach rests on the assumption that terrorist authored accounts are more than post-hoc rhetorical exercises that aim to persuade others, or even the authors themselves, of the righteousness of their political cause or otherwise mitigate their responsibility for their involvement in violence. In particular, I advance a framework for methodically applying narrative approaches to terrorist authored texts, in particular, autobiographies. In doing so, I will demonstrate how this approach can help better comprehend how individuals involved in militancy understand the world, draw upon existing narrative resources and give meaning to their actions.